ANALYSIS OF BROTHER ANGELO CHILD SEXUAL ABUSE CASE UNDER CRIMINAL LAW AND CONTROL THEORY - Abraham Misael Halim; Andre Sandy (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The topic of child sexual abuse and child abuse in general has been a growing topic within Indonesia, as awareness of the issue nationwide has risen within past years. One landmark case of child sexual abuse in Indonesia is about brother Angelo, the founder of Kencana Bejana Rohani orphanage who was allegedly arrested for sexually abusing at least 3 children in his own orphanage. This academic journal will focus on analyzing the positive criminal laws and regulation surrounding Angelo’s crime of child sexual abuse as well as examining the brother Angelo case under Travis Hirschi’s control theory. This research is conducted under normative legal research method that relies on data available and deriving a qualitative analysis.